2020
DOI: 10.1002/gps.5306
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of accidents in people with mild cognitive impairment, mild dementia due to Alzheimer's disease and healthy controls in simulated driving

Abstract: Objectives: To examine the driving variables that predict accident probability in mild dementia due to Alzheimer's disease (AD), mild cognitive impairment (MCI) and healthy older control drivers in simulated driving. To compare the three groups in mean performance and in frequency of scores exceeding 1.5 SD from the mean. Methods/Design: Participants were 37 drivers with MCI, 16 drivers with AD, and 21 control drivers over the age of 52. Driving measures were derived from four rural driving conditions: moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
1
14
0
6
Order By: Relevance
“…1). More precisely, the responses of AD patients were slower than the SCD and MCI groups in simple reaction tests; but in the complex situation, there was no difference among the RT of the three groups (Table 3), which is in line with a recent study [53] reporting that drivers with AD showed significantly greater RT than control drivers in simulated driving. In addition, more than half the participants lacked stability of driving operations (see sim-dRT and com-dRT in Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1). More precisely, the responses of AD patients were slower than the SCD and MCI groups in simple reaction tests; but in the complex situation, there was no difference among the RT of the three groups (Table 3), which is in line with a recent study [53] reporting that drivers with AD showed significantly greater RT than control drivers in simulated driving. In addition, more than half the participants lacked stability of driving operations (see sim-dRT and com-dRT in Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, the simulator software used in our study did not measure the average speed of the participants. Economou et al [53] also pointed out the crawling problem of senior drivers, and interpreted it as a compensatory behavior to cope with the complex simulated traffic. Piersma et al [11] found that patients with AD drove significantly more slowly than healthy participants, when they were in a hurry or at the intersections.…”
Section: Discussionmentioning
confidence: 99%
“…These simulators can collect data on parameters such as braking time and pressure, lane deviation, speed variability, and many other common driving safety errors in routine and high-pressure driving scenarios. Because of the advantage of keeping dependencies required by examining specific correlated driving abilities, simulated driving framework has been popularly applied in determining the correlation between different domains of cognitive deficits and operational driving abilities 16,18,19,21–34. According to the collected papers in this study, simulated driving test also provide the possibility for researchers to explore patients driving performance in some extreme situations (ie, collision,16,29 traffic25).…”
Section: Resultsmentioning
confidence: 99%
“…und ist folgendermaßen aufgebaut: Pre-Test (z. B. Überprüfung von Basiswissen zur Fahrsicher- [24,26,27,29,31,36], insgesamt langsamer fuhren [21][22][23][24]36] und Probleme hatten die Fahrspur zu halten [22,24]. Weitere Auffälligkeiten waren langsamere Reaktionszeiten bei unerwarteten Ereignissen [21][22][23] und besonders großer Abstand zu anderen Fahrzeugen [22,23].…”
Section: Discussionunclassified